1998
DOI: 10.1038/sj.bmt.1701523
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for severe hemorrhagic cystitis following BMT

Abstract: Summary:Hemorrhagic cystitis (HC) is a common toxicity of preparative regimens for bone marrow transplantation (BMT). Severe HC often requires prolonged and expensive hospitalization, and occasionally can result in death. To investigate the risk factors for severe HC, we conducted a retrospective study among 1908 patients who received BMTs at the University of Minnesota during 1974 to 1993. A previous report from our institution reported on 977 of these patients. We identified all patients with genitourinary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
144
0
9

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(160 citation statements)
references
References 26 publications
7
144
0
9
Order By: Relevance
“…BU has been implicated as a risk factor for HC but a dose-dependent correlation has not been reported. 10,[37][38][39] In this study, the subgroup analysis including fludarabine/BU/TBI conditioning showed myeloablative conditioning regimen as a risk factor for HC in multivariate analysis. This analysis could support the dose dependence of BU on the development of BK-HC as Gilis et al 28 suggested a conditioning regimen including 4 days of BU for a risk factor for BK-HC.…”
Section: Discussionmentioning
confidence: 99%
“…BU has been implicated as a risk factor for HC but a dose-dependent correlation has not been reported. 10,[37][38][39] In this study, the subgroup analysis including fludarabine/BU/TBI conditioning showed myeloablative conditioning regimen as a risk factor for HC in multivariate analysis. This analysis could support the dose dependence of BU on the development of BK-HC as Gilis et al 28 suggested a conditioning regimen including 4 days of BU for a risk factor for BK-HC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the ubiquitous use of BU may also explain the lack of difference as other studies have proven BU to be a risk factor of HC development. [24][25][26] As the urinary tract is the main site of BKV latency, it is expected to be the first site of reactivation. Transient BK viruria occurs in all allo-HSCT patients 19 with 4-25% of the patients developing sustained BKV-HC.…”
Section: High Burden Of Bk Virus-associated Hemorrhagic Cystitis L Gimentioning
confidence: 99%
“…Transient BK viruria occurs in all allo-HSCT patients 19 with 4-25% of the patients developing sustained BKV-HC. 8,15,17,19,20,[26][27][28][29] A peak in BK viruria X3 to 6-log correlates with the occurrence of HC. 1,18,29,30 Consistent with these data, all the patients in our study had a BK viruria higher than 10 8 copies/mL indicating that BK viruria may not be the most relevant factor for the prediction of BKV-HC severity.…”
Section: High Burden Of Bk Virus-associated Hemorrhagic Cystitis L Gimentioning
confidence: 99%
“…A wide variety of causal factors can give rise to posttransplant hemorrhagic cystitis (PTHC) as these patients are on various immunosuppressive medications for prevention/therapy of GVHD. The incidence of PTHC among the BMT recipients ranges from 6.5 to 52 % [1,2]. It is characterized by the classical symptoms of lower urinary tract symptoms like dysuria, haematuria, urgency and increased frequency.…”
Section: Discussionmentioning
confidence: 99%